2183. Financial Cost, Length of Stay, and Patient Experience Associated with Healthcare-Associated Infections Across a 43 Hospital Network. (26th November 2018) - Kast, Rachel; Grabow, Cole; Fitch, Michelle; Tobar, Sandra; Malani, Anurag; Olmsted, Russell
Abstract: Background: Reduction of healthcare-associated infections (HAIs) is critical to improve patient safety and hospital quality. However, not all HAI-associated outcomes are well studied. We examined several of these—the financial and length of stay (LOS) burden of HAIs and patient experience of care. Methods: National Healthcare Safety Network-reported catheter-associated urinary tract infections (CAUTI), C. difficile infections (CDI), central line-associated bloodstream infections (CLABSI), MRSA bacteremia, and colon surgery surgical site infections (SSI-COLO) were queried for the first 9 months of 2016 from 43 hospitals. Patients with an HAI were matched to controls on hospital and primary diagnosis to create a retrospective case–control study. CAUTI and CLABSI patients were matched to controls with associated device codes. LOS and total direct variable cost (TDVC) were collected for all HAI and control patients. If patients returned a Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey, their likelihood to recommend (LTR) response was additionally analyzed. Results: Data were analyzed for 123 CAUTI, 1, 116 CDI, 166 CLABSI, 58 MRSA, and 127 SSI-COLO case–control pairs across 43 hospitals. TDVC per case was significantly higher among HAI cases than controls for CDI ($6, 484), CLABSI ($14, 646), and SSI-COLO ($9, 770; figure 1). LOS was significantly higher for cases across all HAI groups, with attributable differences of 7.6 days for CAUTI, 6.4 for CDI, 9.7 for CLABSI, 7.4 for MRSA, and 4.5 for SSI-COLO (Figure 2). Of 3, 180 subjects, 198 returned HCAHPS surveys. Response rate of "Yes, definitely" to LTR for 85 HAI patients was 63.5% compared with 72.6% for 113 control patients (Figure 3). Conclusion: This is the first investigation to our knowledge pairing patient experience of care data with TDVC and LOS for HAI patients. HAIs have a significant impact on patient experience, cost, and length of stay―further supporting the importance of preventing HAIs. Disclosures: R. Olmsted, Ethicon, Inc.: Speaker's Bureau, Speaker honorarium; APIC: External faculty HRET/CDC STRIVE project, Speaker honorarium.